ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI ATAU MERGER PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER DI BEI - Evanlie, Timotius; Hikmah, Nor (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the comparison of financial performance before and after mergers or acquisitions in primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2023. The research method uses a quantitative approach and uses comparative statistical methods. The normality test uses the Shapiro-Wilk method. Data tests for normally distributed data use the Paired Sample T Test. For non-normally distributed data using the Wilxocon Signed Rank Test with SPSS ver. 26. The variables used in this study are Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TOTA), and Return on Equity (ROE). The population in this study were all primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) in the 2013-2023 period. While the sample in this study were 12 samples taken using purposive sampling. The results showed that there were no significant differences in the financial ratios Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turn Over (TOTA), and Return on Equity (ROE) by testing the financial statements 2 years before and 2 years after the merger or acquisition.